THE MODEL OF TRANSFORMATIVE-INTEGRATIVE ISLAMIC EDUCATION (DEVELOPMENT OF EPISTEMOLOGY IN ISLAMIC EDUCATION) - Huda, Nur (Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2019)
The modern education system is based on the paradigm of modern science that is free of value and is positive. This paradigm in its development has contributed greatly to the world of education which has become more measurable, reasonable, directed, and oriented towards providing benefits in life. However, on the other hand simultaneously, the modern paradigm shows several problems. Positivism assumptions show their shortcomings; especially the effects of value-free principles that make the direction of civilization lose the value of togetherness, ecology, and spirituality. Efforts to transform an idea can only be done effectively if through a systematic system of education. Unfortunately, the results of the thoughts of the Muslim scholars have not yet been actualized into the practical area of education. For this reason, this study starts from the actual problem in Islamic thought, namely the idea of social piety, then from that idea it will be formulated into a particular educational model. In simple terms, this study aims to formulate a synthesis of non-educational thinking towards educational thinking that is formulated in the form of models